1993
DOI: 10.1007/bf02072495
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial of albumin infusion in ill preterm infants

Abstract: We assessed the effect of albumin infusion on weight loss and ventilation requirement in sick premature infants. Thirty infants, median gestational age 29 weeks, were entered into a randomised controlled trial, at a median of 2 days of age. The infants, all with an albumin level < or = 30 g/l, received either 5 ml/kg of 20% albumin or 5 ml/kg of their maintenance fluids (placebo), both given as part of the total daily fluid requirement. The response to the infusion was assessed by comparing two periods; 12 h i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1
3

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(25 citation statements)
references
References 13 publications
1
20
1
3
Order By: Relevance
“…there were insufficient or no data to assess other clinically important outcomes). The study by Greenough et al (Greenough 1993) did not to report any of our primary and secondary outcome measures.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…there were insufficient or no data to assess other clinically important outcomes). The study by Greenough et al (Greenough 1993) did not to report any of our primary and secondary outcome measures.…”
Section: Discussionmentioning
confidence: 96%
“…Greenough et al (Greenough 1993) studied the effect of albumin infusion versus placebo on 40 premature infants (28 -34 weeks gestational age, 20 in each group). Study subjects were newborn infants who were ventilator dependant at less than seven days of age and had a serum albumin level of ≤30 g/L.…”
Section: E S C R I P T I O N O F S T U D I E Smentioning
confidence: 99%
“…15 By contrast, the infusion of colloidal fluid during the perinatal period in premature infants of median gestational age 27 weeks has been related to an increased duration of oxygen dependency and abnormal neurodevelopmental outcomes. 16,17 In addition, albumin potentially causes deterioration of the protein leak syndrome of prematurity and lung function by deactivation of the surfactant in alveolar spaces.…”
Section: Discussionmentioning
confidence: 99%
“…ALB-containing solutions are not part of the recommendations because of increased cost, limited availability, a theoretical risk of infectious disease, and in particular a previous observed association with increase mortality in a large meta-analysis of ALB versus crystalloid use across the indications of hypovolemia, burns, and hypoalbuminemia of primarily adult studies (3). Two neonatal trials of hypotensive preterm infants in the neonatal intensive care unit (8,9) were included along with 28 adult trials. Several of the included adult studies suggested that patients who received ALB had worse pulmonary outcomes (10 -12).…”
Section: Discussionmentioning
confidence: 99%